A fuzzy multi-objective programming model for the delivery and distribution of humanitarian relief materials - Chai, Ruirui; He, Hongwei; Liu, Dehai; Chen, Jingfeng (Engineering applications of artificial intelligence, 2024)
Disaster relief presents many unique logistics challenges, including damaged transportation infrastructure, multiple conflicting goals, and secondary disasters caused by spontaneous disaster relief. The delivery and distribution of humanitarian relief materials faced by nonprofit organizations (NPOs) poses a critical challenge due to the highly unpredictable nature of disasters, conflicting missions, and the need to navigate government regulations in disaster management. In this paper, we propose a novel multi-objective disaster relief modeling system for NPOs, considering (1) prioritization (providing medical services to seriously injured victims), (2) effectiveness (degree of satisfaction), (3) efficiency (operational costs), and (4) equity (cost of maintaining order). To incorporate the practical constraints of disaster relief operations, we include factors such as road damage, transportation capacity limitations, and route flow saturation as part of the model formulation. We then utilize fuzzy multi-objective programming to optimize the proposed disaster relief model, considering two relief distribution schemes: a common NPOs' spontaneous relief scheme and a newly designed traffic control scheme with government regulation. Based on the real-world scenario of the 2008 Wenchuan earthquake, we demonstrate that the designed traffic control scheme exhibited remarkable improvement among the NPOs' four objectives compared to the spontaneous relief scheme. Moreover, in the process of solving fuzzy multi-objective programming problems, artificial intelligence technology is employed to handle the fuzziness in multi-objective and automatically adjust parameters, making the solution results better and in line with practical situations. And we also validate the proposed model can be solved in polynomial time, meeting the engineering practice requirements, and can be easily extend to most disaster relief distribution scenarios. [Display omitted] •Fuzzy multi-objective programming model for humanitarian relief materials’ delivery and distribution was built.•Prioritization, effectiveness, efficiency and equity were considered as the NPOs objectives.•Roadway capacity is considered as a constraint condition.•The NPOs’ spontaneous relief scheme and traffic control scheme were discussed specially.•Delivery and distribution of humanitarian relief materials was analyzed based on 2008 Wenchuan earthquake.